2020
DOI: 10.1038/s41598-020-76877-7
|View full text |Cite
|
Sign up to set email alerts
|

The importance of using whole genome sequencing and extended spectrum beta-lactamase selective media when monitoring antimicrobial resistance

Abstract: To tackle the problem of antimicrobial resistance (AMR) surveillance programmes are in place within Europe applying phenotypic methods, but there are plans for implementing whole genome sequencing (WGS). We tested the benefits of WGS using Escherichia coli collected from pig surveillance performed between 2013 to 2017. WGS was performed on 498 E. coli producing ESBL and AmpC enzymes, recovered from pig caeca on MacConkey + cefotaxime (McC + CTX) agar, as recommended by the European Commission, or ESBL agar, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 41 publications
(50 reference statements)
4
32
3
Order By: Relevance
“…The results suggested that the E. coli strains could be randomly spread between the farms in each country. A recent study on E. coli isolates collected from pig surveillance between 2013 and 2017 in the United Kingdom also found no correlation between phylogeny and year of isolation 13 . This suggests that E. coli isolates could be as well randomly spread in countries and through different years.…”
Section: Discussionmentioning
confidence: 93%
“…The results suggested that the E. coli strains could be randomly spread between the farms in each country. A recent study on E. coli isolates collected from pig surveillance between 2013 and 2017 in the United Kingdom also found no correlation between phylogeny and year of isolation 13 . This suggests that E. coli isolates could be as well randomly spread in countries and through different years.…”
Section: Discussionmentioning
confidence: 93%
“…For example, even if the SMX concentration decreased between all input and output samples, sul2 abundance did not depend on sulfonamide presence. The sul2 gene is usually found on small plasmids of the IncQ family [ 50 ], which are multi-resistant plasmids, and some authors [ 51 ] found that its presence could not be ascribed to a single antibiotic, but presumably to several co-selection phenomena [ 52 ]. In a similar way, the gene qepA was ubiquitous in both input and output samples.…”
Section: Discussionmentioning
confidence: 99%
“…The K m of the recombinases was, in both cases, lower than other reported enzymes, which showed better affinity for CGA than others. For example, the K m values of B-type FAE, AoFaeB produced by Neurospora and two FAEB from Aspergillus niger for CGA were 180, 160 and 630 µmol, respectively [12,13,20].…”
Section: Substrate Profile and Kinetic Parametersmentioning
confidence: 99%
“…An Aspergillus strain SD14 was isolated from CGA-rich soil, which could produce an enzyme with CGA hydrolytic activity. Whole genome sequencing (WGS) is the individual genome sequencing of species with unknown genome sequences, which can detect all the genetic information in the genome [12]. The whole genome sequencing analysis showed that the Aspergillus strain SD14 is a strain of Aspergillus aculeatus, and the ferulic esterase is an enzyme capable of hydrolyzing CGA.…”
Section: Introductionmentioning
confidence: 99%